2020
DOI: 10.1101/2020.05.22.111526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico detection of SARS-CoV-2 specific B-cell epitopes and validation in ELISA for serological diagnosis of COVID-19

Abstract: Rapid generation of diagnostics is paramount to understand epidemiology and to control the spread of emerging infectious diseases such as COVID-19. Computational methods to predict serodiagnostic epitopes that are specific for the pathogen could help accelerate the development of new diagnostics. A systematic survey of 27 SARS-CoV-2 proteins was conducted to assess whether existing B-cell epitope prediction methods, combined with comprehensive mining of sequence databases and structural data, could predict whe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The other possibility is the false positive PCR test. In our study as in (Phan, Subramanian et al 2020) detection of anti-RBD IgG yielded more reliable results than other tested antigens. Previously it was demonstrated that titers of anti-SARS-CoV-2 antibodies positively correlate with patient age (Wu, Wang et al 2020).…”
Section: Discussionsupporting
confidence: 66%
“…The other possibility is the false positive PCR test. In our study as in (Phan, Subramanian et al 2020) detection of anti-RBD IgG yielded more reliable results than other tested antigens. Previously it was demonstrated that titers of anti-SARS-CoV-2 antibodies positively correlate with patient age (Wu, Wang et al 2020).…”
Section: Discussionsupporting
confidence: 66%
“…Like Phan et al (2020), we found that detection of anti-RBD IgG yielded more reliable results than other tested antigens. On the other hand, although it was previously demonstrated that titers of anti-SARS-CoV-2 antibodies positively correlate with patient age (Wu et al, 2020a), we did not observe this pattern in our cohort.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, we sought to overcome these limitations in study design and to more comprehensively examine the functional profiles of antigen-specific immune responses and their association with risk factors and clinical outcomes after COVID-19. We leveraged a large cohort of convalescent donors, including individuals recruited as candidate donors for convalescent plasma donation (29) in Seattle, WA, where SARS-CoV-2 community transmission was first described in the United States (30). We selected study participants that were either hospitalized (n=20) or not hospitalized (n=40) after matching for age, sex, ethnicity, and date of symptom onset.…”
Section: Introductionmentioning
confidence: 99%